A cost-effectiveness analysis of first-line induction and maintenance treatment sequences in patients with advanced nonsquamous non-small-cell lung cancer in France - Taipale K; Winfree KB; Boye M; Basson M; Sleilaty G; Eaton J; Evans R; Chouaid C (Dove Medical Press, 2017)
Kaisa Taipale,1 Katherine B Winfree,2 Mark Boye,2 Mickael Basson,3 Ghassan Sleilaty,4 James Eaton,5 Rachel Evans,5 Christos Chouaid6 1Global Patient Outcomes and Real World Evidence International, Oy Eli Lilly Finland AB, Helsinki, Finland; 2Global Patient Outcomes and Real World Evidence, Eli Lilly and Company, Indianapolis, IN, USA; 3Corporate Affairs, Lilly France, Neuilly-sur-Seine, 4Bio-Medicines Medical Affairs, Lilly France, Neuilly-sur-Seine, France; 5ICON Health Economics and Epidemiology, ICON Plc, Milton Park, UK; 6Thoracic Oncology, Service de Pneumologie, Centre Hospitalier Intercommunal Créteil, Créteil, France Background: Comparative effectiveness and cost-effectiveness data for induction–maintenance (I–M) sequences for the treatment of patients with nonsquamous non-small-cell lung cancer (nsqNSCLC) are limited because of a lack of direct evidence. This analysis aimed to compare the cost-effectiveness of I–M pemetrexed with those of other I–M regimens used for the treatment of patients with advanced nsqNSCLC in the French health-care setting. Materials and methods: A previously developed global partitioned survival model was adapted to the France-only setting by restricting treatment sequences to include 12 I–M regimens most relevant to France, and incorporating French costs and resource-use data. Following a systematic literature review, network meta-analyses were performed to obtain hazard ratios for progression-free survival (PFS) and overall survival (OS) relative to gemcitabine + cisplatin (induction sequences) or best supportive care (BSC) (maintenance sequences). Modeled health-care benefits were expressed as life-years (LYs) and quality-adjusted LYs (QALYs) (estimated using French EuroQol five-dimension questionnaire tariffs). The study was conducted from the payer perspective (National Health Insurance). Cost- and benefit-model inputs were discounted at an annual rate of 4%. Results: Base-case results showed pemetrexed + cisplatin induction followed by (→) pemetrexed maintenance had the longest mean OS and PFS and highest LYs and QALYs. Costs ranged from €12,762 for paclitaxel + carboplatin → BSC to €35,617 for pemetrexed + cisplatin → pemetrexed (2015 values). Gemcitabine + cisplatin → BSC, pemetrexed + cisplatin → BSC, and pemetrexed + cisplatin → pemetrexed were associated with fully incremental cost-effectiveness ratios (ICERs) of €16,593, €80,656, and €102,179, respectively, per QALY gained versus paclitaxel + carboplatin → BSC. All other treatment sequences were either dominated (ie, another sequence had lower costs and better/equivalent outcomes) or extendedly dominated (ie, the comparator had a higher ICER than a more effective comparator) in the model. Sensitivity analyses showed the model to be relatively insensitive to plausible changes in the main assumptions, with none increasing or decreasing the ICER by more than ~€20,000 per QALY gained. Conclusion: In the absence of direct comparative trial evidence, this cost-effectiveness analysis indicated that of a large number of I–M sequences used for the treatment of patients with nsqNSCLC in France, pemetrexed + cisplatin → pemetrexed achieved the best clinical outcomes (0.28 incremental QALYs gained) versus paclitaxel + carboplatin → BSC. Keywords: advanced nonsquamous NSCLC, cost-effectiveness, France, induction–maintenance, pemetrexed, quality-adjusted life-years